การปรับปรุงคุณสมบัติกำลังรับแรงอัดของดินลูกรังโดยการใช้ซีเมนต์และกากยิปซัม - จักรพันธ์ ธงทอง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research present results of a laboratory study on effects of waste gypsum additive on the compressive strength behaviors of cement stabilized lateritic soils. Two lateritic soil samples of different plasticity were purposely selected from natural borrow pits for this study. The soil samples were subjected to laboratory trial mix studies by mixing with various rate of cement and waste gypsum, compacted and cured into hardened specimen before subjected to unconfined compression test to investigate the compressive strength behaviours. Effects of wet and dry curing condition on the strength behaviours were also included in the test series to establish long term stability. Chemical properties of selected hardened stabilized soil samples were additionally exammed by SEM (microstructure study), XRF (chemical composition study) and XRD (mineral composition study) techniques. Results of the unconfined compression tests had shown that compressive strength of the stabilized soil increased to a maximum value with the increase in amount of gypsum additive up to about 3-4%. Further increase in the amount of gypsum additive above the 3-4% range resulted in strength reduction from the maximum value while the samples over expanded to cause crack formation. The soils of high PI was found to give better response to gypsum additive and showed higher strength merease. The soil of high PI with 3% gypsum additive have shown strength increase of 62% compare with that without gypsum. While the soil of low PI with 4% gypsum additive have shown only 32% strength increase. From the relationship between strength values and curing time, the increase in strength values during later curing time for sample with gypsum additive were clearly higher than those without gypsum. The soil of high PI with 2-3% gypsum additive have shown about 20% strength increase during the curing age of 28-56 days compare to only 7% increase for the case of no gypsum additive. This seems to be in consistent with the hypothesis that increase in strength due from the occurrence of ettringite in pozzolanic reaction was much slower than that from the reaction of cement hydration. Elastic modulus of the stabilized samples with gypsum additive were found to be reducing in reverse of the strength increase. This is in contrast with the general trend of cement stabilized soils. This confirm the mechanism of strength increase by occurrence of ettringite to fill void of gypsum stabilize soils. As for the effect of wet and dry curing conditions which would generally resulting in strength reduction, it was found that for the high PI soils, strength reduction in the case of cement stabilized samples with gypsum addition were comparable with those without gypsum additive. However for the soil with low PI, the strength reduction for the case of sample with gypsum additive were much greater. This indicate that careful consideration has to be employed in selecting the type of soil for gypsum stabilization to avoid undesirable effect on long term stability. Results of the chemical composition and mineral examination confirmed the occurrence of ettringite expanding to fill soil pore in stabilized samples with gypsum additive. It is therefore can be anticipated that the occurrence of ettringite was responsible for higher strength with lower elastic modulus in cement-gypsum stabilization as compared to normal cement stabilization. In an overall view, it can be concluded from the result of this study that appropriate quantity of gypsum additive to soil cement stabilization can result in additional strength increase, reduce shrinkage, and lowered elastic modulus. This overall effects can result in soil cement of good strength performance and long term durability. However, careful application must be exercised to ensure that the gypsum additive will not be overdosed to cause reverse effects. Careful selected application to appropriate soil with relatively high clay content is also important to ensure long term stability.